Artificial intelligence and copyright - Souza, Paulo Vítor (2021)
Artificial Intelligence is one of the emerging technologies with the most potential nowadays. The scale of use is increasingly broad, and many companies are involved in developing this technology with significant investments. In this sense, intellectual property issues have been raised in several legal systems, with different approaches. Knowing who owns the copyright of works produced by an AI is crucial as it will directly impact the development of this technology. Furthermore, it is paramount for fully autonomous AI, as there is no human intervention in these. Another path would be creating a robotic legal personality, which raises ethical and legal issues that will take time to overcome.